2018
DOI: 10.1371/journal.pone.0195405
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between food waste, diet quality, and environmental sustainability

Abstract: Improving diet quality while simultaneously reducing environmental impact is a critical focus globally. Metrics linking diet quality and sustainability have typically focused on a limited suite of indicators, and have not included food waste. To address this important research gap, we examine the relationship between food waste, diet quality, nutrient waste, and multiple measures of sustainability: use of cropland, irrigation water, pesticides, and fertilizers. Data on food intake, food waste, and application … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
217
11
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(238 citation statements)
references
References 39 publications
7
217
11
3
Order By: Relevance
“…It is noteworthy that, especially for the 507 texture attribute, the cake that was the least well received by the panelists was the one 508 without addition of MSF. Conrad et al [53], studying the properties of melon seed 509 flour, maazoun variety, confirmed that the emulsifying ability of this product presented 510 better results than wheat flour, confirming that melon seed meal can potentially be 511 added to products of baking.…”
mentioning
confidence: 92%
“…It is noteworthy that, especially for the 507 texture attribute, the cake that was the least well received by the panelists was the one 508 without addition of MSF. Conrad et al [53], studying the properties of melon seed 509 flour, maazoun variety, confirmed that the emulsifying ability of this product presented 510 better results than wheat flour, confirming that melon seed meal can potentially be 511 added to products of baking.…”
mentioning
confidence: 92%
“…Another study performed an exploratory online survey using a questionnaire adapted for studies on FW [24]. Furthermore, multivariate analyses was carried out for a comparative analysis of the environmental characteristics of the EU Member States with different agricultural systems [26].…”
Section: Methodsmentioning
confidence: 99%
“…Conrad et al [26] analyzed the link between FW, diet quality, nutrient waste and sustainability in the US. Higher quality diets lead to higher FW associated with greater amounts of wasted irrigation water and pesticides but less cropland waste due to the increasing consumption of fruits and vegetables included in higher quality diets, which have lower cropland and higher input needs compared to other crops.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These observations, as well as the amount of food wasted, indicates that the residents are not only able to gain access to a variety of nutritional food, but also access to a large quantity of it, thus highlighting a problem of oversupply and wasted resources. Food waste, unfortunately, is a critical indicator of sustainability, as it represents the amount of resources throughout the food production process that are wasted in order to produce uneaten food [9]. Besides that, Food waste also contribute to greenhouse gaseous emission from the decomposition process [10].…”
Section: Food Wastementioning
confidence: 99%